2013
DOI: 10.1371/journal.pone.0071041
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Injection of Apelin-Overexpressing Bone Marrow Cells Improves Cardiac Repair via Upregulation of Sirt3 after Myocardial Infarction

Abstract: Our previous study shows that treatment with apelin increases bone marrow cells (BMCs) recruitment and promotes cardiac repair after myocardial infarction (MI). The objective of this study was to investigate whether overexpression of apelin in BMCs improved cell therapy and accelerated cardiac repair and functional recovery in post-MI mice. Mouse myocardial infarction was achieved by coronary artery ligation and BMCs overexpressing apelin (apelin-BMCs) or GFP (GFP-BMCs) were injected into ischemic area immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 39 publications
9
57
0
Order By: Relevance
“…This in turn improves myocardial hypertrophy and remodelling and results in maintaining myocardial tissue integrity. In line with this study, Li et al [28] reported that myocardial injection of apelin overexpressing bone marrow cells immediately after MI in mice decreased apoptosis. They also reported that treatment with apelin-13 (1 mg/kg/day) for three days before MI and for 14 days post-MI decreased myocardial apoptosis and hypertrophy [29].…”
Section: Discussionsupporting
confidence: 77%
“…This in turn improves myocardial hypertrophy and remodelling and results in maintaining myocardial tissue integrity. In line with this study, Li et al [28] reported that myocardial injection of apelin overexpressing bone marrow cells immediately after MI in mice decreased apoptosis. They also reported that treatment with apelin-13 (1 mg/kg/day) for three days before MI and for 14 days post-MI decreased myocardial apoptosis and hypertrophy [29].…”
Section: Discussionsupporting
confidence: 77%
“…The result presented here shows decreased miR-335 expression levels in patients with HCC, which is consistent with a recent report indicating that miR-335 is reduced in HCC via aberrant promoter hypermethylation [35]. Besides, we found that HCC patients with low miR-335 levels depicted an unfavorable clinicopathologic features (high AFP values, vascular invasion, cirrhosis and large tumor volume), and those patients also had a poor response to TACE.…”
Section: Discussionsupporting
confidence: 92%
“…Autophagy has been reported to play a protective role in the heart following myocardial ischemia/reperfusion. In our previous study, we showed that treatment of post-MI mice with apelin-BMCs increased the expressions of autophagy gene LC3-II/I and Beclin-1 [21]. Some other researchers also reported that apelin/APJ might be related to the process of autophagy.…”
Section: Discussionmentioning
confidence: 87%